Mid- and long-term risk of atrial fibrillation among breast cancer surgery survivors - Yong‐Moon Park; Wonyoung Jung; Yohwan Yeo; Sang Hyun Park; Michael G. Fradley; Sindhu Janarthanam Malapati; Tushar Tarun; Vinay Raj; Hong Seok Lee; Tasneem Z. Naqvi; Ronda Henry‐Tillman; Jawahar L. Mehta; et al. (2024)
The risk of incident atrial fibrillation (AF) among breast cancer survivors, especially for younger women, and cancer treatment effects on the association remain unclear. This study aimed to investigate the risk of AF among breast cancer survivors and evaluate the association by age group, length of follow-up, and cancer treatment.